Articulate Storyline Media-Based Discovery Learning to Improve Students' Mathematical Concept Understanding Ability of Flat-Sided 3D Space - Laila Fitriana; Mukti, Putri Sari; Setiawan, Rubono (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini bertujuan untuk mengembangkan dan menilai apakah media pembelajaran berbasis discovery learning berbantuan Articulate Storyline valid, praktis, dan efektif dalam meningkatkan pemahaman konsep matematika siswa terkait materi bangun ruang sisi datar. Penelitian ini merupakan jenis penelitian pengembangan (R&D) yang mengikuti langkah-langkah model pengembangan ADDIE. Subjek penelitian adalah siswa kelas VIII D di SMP Negeri 23 Purworejo. Metode pengumpulan data yang digunakan adalah observasi, wawancara, kuesioner, dan tes. Analisis data menggunakan perhitungan persentase untuk analisis kevalidan dan kepraktisan, serta uji N-Gain dan Wilcoxon Sign berdasarkan hasil pre-test dan post-test untuk menilai keefektifan produk. Hasil uji validitas menunjukkan skor rata-rata 78,33% dari ahli materi dan 80,43% dari ahli media; hasil uji praktikalitas menunjukkan skor rata-rata 84,75% dari penilaian siswa dan 80,56% dari penilaian guru; dan hasil uji tanda Wilcoxon menunjukkan bahwa skor post-test lebih tinggi dari skor pre-test, dengan rata-rata N-Gain 0,44, yang termasuk dalam kategori peningkatan sedang. Kesimpulannya, media pembelajaran yang dikembangkan valid, praktis, dan efektif dalam meningkatkan pemahaman konsep matematika siswa terkait materi bangun ruang sisi datar. This study aimed to develop and assess whether the discovery learning-based learning media, supported by Articulate Storyline, is valid, practical, and effective in improving students' understanding of mathematical concepts related to flat-sided space buildings. This research is a type of development study (R&D) that follows the ADDIE development model steps. The research subjects were students of class VIII D at SMP Negeri 23 Purworejo. Data collection methods included observation, interviews, questionnaires, and tests. Data analysis involved percentage calculations for validity and practicality analysis, as well as N-Gain and Wilcoxon Sign tests based on pre-test and post-test results to assess the effectiveness of the product. The validity test results showed an average score of 78.33% from material experts and 80.43% from media experts; The practicality test results showed an average score of 84.75% from student assessments and 80.56% from teacher assessments; and The Wilcoxon sign test results indicated that the post-test score was higher than the pre-test score, with an average N-Gain of 0.44, which falls under the moderate improvement category. In conclusion, the developed learning media is valid, practical, and effective in improving students' understanding of mathematical concepts related to flat-sided space buildings.